2019
DOI: 10.1249/jes.0000000000000201
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Regulation of Muscle Regrowth From Disuse in Aging

Abstract: Skeletal muscle immune cells, such as macrophages, are necessary for proper regrowth after muscle disuse. We suggest that the important role of macrophages concerning muscle regrowth after disuse is divergent compared with young mice (i.e., dysregulated) during the recovery period. Modulation of macrophages may be a promising future therapeutic target to enhance the impaired muscle growth during recovery from disuse in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 65 publications
0
11
1
Order By: Relevance
“…Progressive impairment of skeletal muscle function with aging has been linked to disequilibrium between muscle damage and repair (Cui et al, 2019;Reidy et al, 2019). The findings in our study display some discrepancies between young and old subjects which may relate to this.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Progressive impairment of skeletal muscle function with aging has been linked to disequilibrium between muscle damage and repair (Cui et al, 2019;Reidy et al, 2019). The findings in our study display some discrepancies between young and old subjects which may relate to this.…”
Section: Discussioncontrasting
confidence: 47%
“…Studies have demonstrated that uninjured muscle in elderly individuals contains a predominance of anti-inflammatory macrophages (Cui et al, 2019;Reidy et al, 2019) which has been associated with the development of fibrosis (Mann et al, 2011) although it is possible that macrophage content increases to combat fibrosis rather than contributing to it. Indeed it has been shown that resident anti-inflammatory muscle macrophages are associated with exercise−mediated increases in skeletal muscle fiber size, suggesting a role in muscle growth (Walton et al, 2019a).…”
Section: Discussionmentioning
confidence: 99%
“…Disrupted skeletal muscle repair with aging and chronic disease has been described, though mechanistic explanations often focus on sex hormones, satellite cells, or intrinsic structural dysmorphias. Despite the understood immune changes with aging and disease and the established roles of monocytes in skeletal muscle homeostasis, our understanding of the relationship between the immune system and musculoskeletal system under such conditions is in its infancy ( Cui et al, 2019 ; Reidy et al, 2019a ). Immunological investigation into muscular dystrophy demonstrated that dystrophic mice had profound increases in total muscle MΦs and targeting this infiltration can mitigate disease progression ( Mojumdar et al, 2014 ; Villalta et al, 2015 ).…”
Section: Immune Cellsmentioning
confidence: 99%
“…Additional research is warranted to delineate the capacity for inflammation to regulate signaling between different cell types in skeletal muscle that is involved in maintaining metabolic and protein turnover homeostasis. Immune cells comprise 2–6% of skeletal muscle’s cell population, but maintain a well-established role in skeletal muscle homeostasis, especially macrophages (MΦ; Tidball, 2002 ; Reidy et al, 2019a ). While the understanding of the MΦ’s role in skeletal muscle repair and remodeling is well-appreciated, there is strong evidence for both T-cells and neutrophils in the maintenance of skeletal muscle MΦ function and overall skeletal muscle plasticity ( Frenette et al, 2002 ; Tidball, 2005 ; Dumont et al, 2008 ; Schiaffino et al, 2017 ; Tidball, 2017 ; Deyhle and Hyldahl, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation